Ethiopia's government adopts a National Framework for Climate Services (NFCS) through consultative processes - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
CCAFS supported the Ethiopian Government to develop and adopt a National Framework for Climate Services (NFCS) to guide development of services that better meet the development and adaptation needs of agriculture and other priority sectors. Building on CCAFS agricultural climate services experience and recent synthesis and guidance publications, CIMMYT contributed to the text, and supported stakeholder engagement and baseline assessment activities; and IRI contributed to recommendations and revised theory of change to better align the NFCS to development impact.